Baicalein—A Potent Pro-Homeostatic Regulator of Microglia in Retinal Ischemic Injury - Pan, Li; Sze, Ying Hon; Yang, Menglu; Tang, Jing; Zhao, Siming; Yi, Irvin; To, Chi-Ho; Lam, Chuen; Chen, Dong Feng; Cho, Kin-Sang; Do, Chi-Wai (Frontiers in Immunology, 2022)
Retinal ischemia is a common cause of many retinal diseases, leading to irreversible vision impairment and blindness. Excessive neuroinflammation, including microglial activation and T cell responses, has been identified as a critical factor associated with neurodegeneration in retinal ischemia. Baicalein is a natural flavonoid reported to have broad anti-inflammatory and neuroprotective bioactivities. Herein, the effects of baicalein on microglia activation in vitro and in vivo were investigated. We found that baicalein exhibited robust anti-inflammatory effect on cultured human and mouse microglia, as demonstrated by decreased induction of pro-inflammatory cytokines and the phosphorylation of phosphoinositide 3-kinase (PI3K) and nuclear factor kappa B (NFκB). Proteomic analysis further unraveled baicalein’s effect on modulating IL-17 signaling pathways and its upstream regulator IL-1β. Intravitreal administration of baicalein in the mouse model of retinal ischemia/reperfusion (I/R) injury attenuated microglial activation and retinal T cell infiltration, particularly the T helper 17 cells. Additionally, baicalein was shown to exert neuroprotective effects by significantly reducing the retinal ganglion cells (RGCs) loss after I/R injury, leading to an improved retinal function and spatial vision. These results suggest that baicalein, a natural flavonoid, acts as a negative regulator of activated microglia and immune responses both in vitro and in vivo, effectively alleviating neurodegeneration in retinal I/R injury. This finding indicates that baicalein could be a potential therapeutic agent to currently incurable degenerative retinal diseases.